Physics Teachers’ Discourses on the Origin of the Universe and the Impact of Personal Beliefs in the Classroom - Aguiar, Matheus Henriques Ribeiro de [UNESP]; Nardi, Roberto [UNESP] (The University of Sydney Library, 2024)
Conflicts in regular education classrooms due to differing personal views on scientific knowledge are recurrent. This article is motivated by enquiries into the significance of the topic of “the origin of the universe” in the context of elementary school curriculum, as well as concerns regarding how educators handle this topic, their academic preparation to take this tack, and the impact of students’ and teachers’ own personal beliefs on the classroom setting. Focusing on this topic, we investigated the discourses of teachers with a degree in physics, educated at the same public institution, under the same curricular framework, considering their training, teaching methods, and personal convictions. The study was conducted with open-ended interviews designed to be used in a video-communication setup. Through our analysis, it was possible to verify that teachers feel unprepared to handle the issue in the classroom due to the cultural diversity of their students and the need for greater scientific knowledge. In addition, it was determined that everyone has an independence stance about the connection between faith and science, which reduces the likelihood of conflict.
Keywords: Science; teacher practice; teacher training; Universe